Autismo: fatores relacionados a idade de diagnóstico - Madaschi, Vanessa (2021)
The objective of this study was to investigate the factors related to the age of diagnosis of autism spectrum disorder (ASD) and to carry out a survey of the guarantees of rights achieved by this population in Brazil. With this, we sought, through a scope review, to investigate the age of the first signs and the diagnosis of children with ASD and to map the associated factors directly related to children, families and environmental factors. Twenty-eight studies were selected. The results showed that the age of the first concerns was between 17 and 29.7 months and the age of diagnosis varied between 12 and 103 months of age. The studies also revealed a wide variation in the interval, from two to four years between the first concerns until the moment of diagnosis. At the same time, through a dissertation review, sought to identify the main factors associated with age at diagnosis of ASD to survey the guarantees of the rights of this population in Brazil, seeking to understand that only from the end of the 1980s, relevant actions were launched in relation to the rights of people with disabilities, ensuring the exercise of individual and social rights. According to studies from different regions of the world, the main barriers to an earlier diagnosis of ASD are: i) less severe symptoms (that is, milder cases are detected later); ii) low family socioeconomic status; iii) delay in the parents' concern with the initial symptoms; iv) place of residence of the family (rural area); v) lack / limitation of community resources and organization of public policies, and vi) relationship problems or lack of trust / access of family members to health and education systems. In addition, it was found the importance of facing barriers related to diagnosis, ensuring that it is performed early and the understanding that historically, people with ASD face discrimination and barriers that hinder access to health and their social rights.